Analisis Pengaruh Penerapan Akuntansi Pertanggungjawaban, Manajemen Risiko, dan Kualitas Sumber Daya Manusia Terhadap Akuntabilitas Keuangan Balai Pengelolaan Sumber Daya Air Pemali Comal - Narendra Ahmad Widura; Dumadi; Roni; Mohamad Badrun Zaman; Kukuh Arianto Wibowo; Lintang Prahita Ningarum (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
Financial accountability in the public sector is vital for transparency, public trust, and service quality. This study examines the effects of responsibility accounting, risk management, and human resource quality on financial accountability at the Pemali Comal Water Resources Management Center using a quantitative explanatory approach. Data were collected from 82 employees through questionnaires and analyzed with multiple linear regression. The results show that responsibility accounting (β = 0.246; sig = 0.016), risk management (β = 0.293; sig = 0.002), and human resource quality (β = 0.307; sig = 0.000) each have a positive and significant effect on financial accountability. Simultaneously, all variables significantly influence financial accountability (F = 24.120; sig = 0.000), with an R² of 0.481, indicating that 48.1% of the variance is explained by the model. These findings emphasize the importance of strengthening accountability systems, effective risk management, and improving human resource quality to enhance financial governance in public sector institutions